A microcomputer assisted method for obtaining composite pictures of focal brain damage. Issue 11 (November 1984) - Fowler, C J; Allen, C M; Hoare, R D; Harrison, M J
Abstract : A method used to produce composite drawings of superimposed areas of brain infarction is described. The method uses a microcomputer interfaced to a digitising pad and linear plotter. Areas of brain damage are drawn on standardised maps, digitised, manipulated in computer memory, and summated using computer graphics facilities. The composites show the position of brain damage in groups of patients as a contour map of the extent of lesion overlap. The method can be used to study neurological and neuropsychological deficits using CT-scan, or other imaging techniques. Deep and superficial lesions may be displayed equally well.